The enterpreneurial journalism in front of its consolidation challenge - Casero-Ripollés, Andreu (Anuario ThinkEPI, 2016)
The creation of media by journalists has seen a strong increase in Spain in recent years in tandem with the crisis experienced within the news sector. This phenomenon, known as entrepreneurial journalism, is a case of innovation within the field of information. The aim of this paper is to critically examine the contributions of entrepreneurial journalism in the fields of information, labor, and business; examine its socio-political effects; and its chances of consolidation. To do this, the challenges it faces to ensure survival are analyzed.
Keywords: News media; Entrepreneurship journalism; Business models; Media companies; Digital journaÂlism